Optimization of precast slab loading in prefabrication by applying Tekla's Stacker and Organizer tool in the multifamily housing project sector - Carhuachin Solorzano, Anderson Jhim (2024)
The problem of precast slab stacking in Lima, Peru, emerges as a critical challenge that impacts efficiency and safety in construction. The need to optimize this process lies in the logistical complexity, where proper handling and placement require specialized machinery and sufficient space. The inherent fragility of precast elements increases the risk of loss or damage during transport, intensifying the urgency to perfect stacking. In the initial phases of the multifamily housing project with the precast company, meticulous planning of the process sequence, along with the implementation of tools such as Stacker and Organizer in Tekla, laid the foundation for efficient schedule management and 3D handling of the precast slabs to the truck. The proposed solution, which includes the implementation of Tekla and the "Stacker" tool, shows a remarkable improvement in slab stacking performance, increasing from 2400 m2/day to 4800 m2/day, and in truck loading, increasing from 801.6 m2/day to 960 m2/day. This effective integration optimizes process planning and sequencing, reducing errors and improving operational efficiency and safety. These results support the conclusion that this combination optimizes the management of pre-slabs, improving stacking efficiency at the construction site in a tangible way.